Instantaneous self-recovery and ultra-low detection limit hydrogel electronic sensor for temporomandibular disorders intelligent diagnosis - Yujie Yan; Lixia Yu; Xuefeng Zhang; Qi Han; Zhixin Yang; Xingyuan Lu; Jiongke Wang; Hao Xu; Qianming Chen; Hang Zhao (Nature Communications)
Abstract Temporomandibular disorders (TMD) intelligent diagnosis promises to elevate clinical efficiency and facilitate timely TMD management for patients. However, development of TMD intelligent diagnostic tools with high accuracy and sensitivity presents challenges, particularly in sensing minute deformations and ensuring rapid self-recovery. Here we report a biocompatible hydrogel electronic sensor with instantaneous self-recovery (within 2.1 s) and ultra-low detection limit (0.005% strain). It could efficiently diagnose disc displacement with reduction (DDwR) with satisfactory accuracy of 90.00%, and also had a clear indication of the typical clinical manifestations of DDwR and the timing of temporomandibular joint (TMJ) clicking, with a sensitivity of up to 100% in human compared to the diagnostic criteria for TMD (DC/TMD). Furthermore, a predictive model based on waveform features achieved 84.4% accuracy and 86% sensitivity, reducing dependence on physicians. In summary, the hydrogel sensor is expected to become a radiation-free, non-invasive, practical and effective tool for future TMD diagnosis.